Makna Komunikasi Pengguna Fitur Obrolan Permainan Hago dalam Menemukan Pasangan - Tantri Puspita Yazid; Heriyanto Tampubolon (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2022)
This study aims to determine the meaning of communication given by users to others through the Hago game chat room feature in finding a partner. Will see the content of messages, speech acts, episodes, relationships, life scripts, to cultural patterns that occur. Using qualitative research methods with a descriptive approach and analyzed with the theory of coordinated meaning management. The subjects in this study were users of the Hago game who were then selected based on a purposive technique. Data was collected through observational studies, interviews, and documentation with four pairs of informants. Data analysis techniques by reducing data, presenting data, and drawing conclusions. In addition, the technique of checking the validity of the data uses source triangulation. The results showed that there were content of messages, speech acts, episodes, relationships, life scripts by users of the Hago game to find their partner. There is a continuation to a more serious level because they have trusted each other. The relationship that exists is also increasingly intense between couples because the chat room feature can make them interact with each other. Although there are cultural differences regarding ethnicity, it is not a problem for couples and families of existing couples. Because for them a sense of love and mutual comfort is the main key to the relationship that occurs. Keywords: hago game, communication, couple